2018
DOI: 10.1182/blood-2017-06-790204
|View full text |Cite
|
Sign up to set email alerts
|

Decitabine enhances targeting of AML cells by CD34+ progenitor-derived NK cells in NOD/SCID/IL2Rgnull mice

Abstract: Combining natural killer (NK) cell adoptive transfer with hypomethylating agents (HMAs) is an attractive therapeutic approach for patients with acute myeloid leukemia (AML). However, data regarding the impact of HMAs on NK cell functionality are mostly derived from in vitro studies with high nonclinical relevant drug concentrations. In the present study, we report a comparative study of azacitidine (AZA) and decitabine (DAC) in combination with allogeneic NK cells generated from CD34 hematopoietic stem and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 43 publications
3
28
0
Order By: Relevance
“…Xu H et al [65] found that DNTs combined with gemcitabine had a better inhibitory effect on transplanted pancreatic tumors in mice. It was also reported that doxorubicin and bortezomib could upregulate the expression of NKG2D and DNAM-1 ligands on melanoma cells [108][109][110][111], promoting more effective DNT killing of tumor cells.…”
Section: Applications Of Dntsmentioning
confidence: 96%
“…Xu H et al [65] found that DNTs combined with gemcitabine had a better inhibitory effect on transplanted pancreatic tumors in mice. It was also reported that doxorubicin and bortezomib could upregulate the expression of NKG2D and DNAM-1 ligands on melanoma cells [108][109][110][111], promoting more effective DNT killing of tumor cells.…”
Section: Applications Of Dntsmentioning
confidence: 96%
“…Thereby, they can improve AML recognition and promote priming of tumour-reactive T cells (Cruijsen et al, 2016;Srivastava et al, 2016). Recently, we also observed that HMA, specifically decitabine, potentiate AML-reactive NK cell responses (Cany et al, 2017). HMA may further modulate tumour immunogenicity by up-regulation of immune stimulatory molecules, including CD80, CD86, ULBP and MIC-A (Zimmer et al, 2008;Yang et al, 2014).…”
Section: Checkpoint Interference and Hypomethylating Agentsmentioning
confidence: 94%
“…The DNA methyltransferase inhibitor azacitidine/5‐azacytidine is a chemical analog of nucleoside cytidine used to treat AML and myelodysplastic syndromes. Decitabine was reported to increase NK‐cell effector function, 41 in addition to their maturation and infiltration into tumor site 42 . The mechanism of action of decitabine on NK cells can be explained by the epigenetic induction of gene expression of cytokines and cytotoxic molecules such as perforin or TRAIL 42 …”
Section: Pharmacological Targets Of Nk‐cell Activationmentioning
confidence: 99%